P682 Predictors of response to biologics in Ulcerative Colitis: A population-based study from the epi-IIRN. (21st January 2022) - Atia, O; Lujan, R; Greenfeld, S; Kariv, R; Matz, E; Dotan, I; Nevo, D; Turner, D
Abstract: Background: Identifying prognostic factors of therapeutic failure, may facilitate balancing the risks and benefits of biologic treatment. In this population-based study, we aimed to explore predictors of therapeutic failure of biologics in Ulcerative Colitis (UC). Methods: We retrieved data from two of four Health Maintenance Organizations in Israel, covering 38% of the population and part of the validated epi-IIRN IBD cohort. We included an inception cohort of UC patients, diagnosed since 2005, who were commenced on biologics. Those who underwent colectomy within 90 days from diagnosis were excluded. The primary outcome was therapeutic failure (i.e. discontinuation of treatment or need for colectomy or >1 short steroid courses). The secondary outcome was primary non-response (PNR; i.e. therapeutic failure within 4 months of initiation). Predictors were sought through Cox proportional hazard model. Results: A total of 910 patients were included (246 [27%] pediatric-onset, 664 [73%] adults) with a median follow-up of 7.9 years (IQR 4.9–12.0). The probability of PNR was 16% and of therapeutic failure 35%, 55% and 63% after one, three and five years after commencing biologics, respectively. Older age at diagnosis (HR 1.01 [95%CI 1.005–1.01]), number of flares prior to initiation of biologics (HR 1.1 [95%CI 1.05–1.2]) and steroid use prior to biologics (HR 1.3 [95%CI 1.1–1.6]) were associated with therapeutic failure. PNR was associated with use of steroids prior to initiation of biologics (HR 2.1 [95%CI 1.4–3.3]). Laboratory blood work, including CRP, ESR, albumin, leukocytes, hemoglobin and platelets did not predict therapeutic failure, whether at diagnosis (HR 1.1 [95%CI 0.6–2.0]) or at initiation of biologics (HR 1.2 [95%CI 0.7–2.1]). Conclusion: One third of UC patients failed to response to biologic treatment within one year. Older age at diagnosis and disease severity prior to biologic treatment, reflected by number of flares and steroid use, predicted therapeutic failure.